Associations between metabolic score for visceral fat and urinary incontinence among US adult women: a population-based cross-sectional study - Chenle Ye; Weikai Huang; Yuanrun Liu; Guangzhan Chen; Siyuan Du; Kaishu Li (BMC Public Health)
Abstract Background This study aimed to elucidate the association between metabolic score for visceral fat (METS-VF) and urinary incontinence (UI) prevalence among adult women in the US. Methods Using data from the National Health and Nutrition Examination Survey (NHANES, 2007–2016), the study conducted a cross-sectional analysis of 4,190 adult women aged ≥ 20 years. The investigation evaluated the relationship between METS-VF and the prevalence and severity of three types of UI: stress urinary incontinence (SUI), urgency urinary incontinence (UUI), and mixed urinary incontinence (MUI). Weighted multivariable logistic regression models and restricted cubic splines (RCS) were employed to assess these associations. Subgroup analyses and interaction tests were performed to explore potential modifying factors. Results METS-VF was positively associated with the prevalence of SUI, UUI, and moderate to severe UI in the fully adjusted model. After categorizing METS-VF into quartiles, higher METS-VF quartiles were linked to increased susceptibility to all UI types, with a notable positive correlation observed for moderate and severe UI. RCS analysis revealed a nonlinear dose-response relationship between METS-VF and both UUI and MUI. Subgroup analyses and interaction tests suggested that age, ethnicity, and vaginal delivery times may influence the positive association between METS-VF and SUI. Conclusion METS-VF was positively associated with UI prevalence (SUI, UUI) and moderate to severe UI. These findings underscore the importance of visceral fat assessment in identifying individuals at risk for UI, offering novel insights for prevention and management strategies. METS-VF may serve as a practical tool for early risk stratification and personalized clinical interventions.